Human-computer trust in navigation systems: google maps vs waze - Trapsilawati, Fitri; Wijayanto, Titis; Jourdy, Eggie Septiawan (Communications in Science and Technology, 2019)
This study investigates users’ trust and reliance toward navigation systems. Forty participants participated in the experiment comparing Google Maps and Waze that have different mechanisms (data-based vs community-based). Our findings revealed that users had higher trust in Waze than Google Maps, due to the higher degree of flexibility in information sharing. Next, we found that users tend to utilize the navigation application that they have used, implying that trust in navigation system is highly associated with trustors’ prior experience and familiarity. Lastly, Google Maps users changed their reliance on Google Maps to Waze upon experiencing Waze features. This study offers several implications that system designers: (i) must ensure that the system’s transparency is maintained, (ii) should profoundly analyze possible interaction between users and computer agents, (iii) should ensure that certain safety conditions are maintained despite the freedom of information sharing provided by the computer agent